Slip‐Stacked J‐Aggregate Materials for Organic Solar Cells and Photodetectors. Issue 22 (19th October 2021) - Kim, Jin Hong; Schembri, Tim; Bialas, David; Stolte, Matthias; Würthner, Frank
Abstract: Dye–dye interactions affect the optical and electronic properties in organic semiconductor films of light harvesting and detecting optoelectronic applications. This review elaborates how to tailor these properties of organic semiconductors for organic solar cells (OSCs) and organic photodiodes (OPDs). While these devices rely on similar materials, the demands for their optical properties are rather different, the former requiring a broad absorption spectrum spanning from the UV over visible up to the near‐infrared region and the latter an ultra‐narrow absorption spectrum at a specific, targeted wavelength. In order to design organic semiconductors satisfying these demands, fundamental insights on the relationship of optical properties are provided depending on molecular packing arrangement and the resultant electronic coupling thereof. Based on recent advancements in the theoretical understanding of intermolecular interactions between slip‐stacked dyes, distinguishing classical J‐aggregates with predominant long‐range Coulomb coupling from charge transfer (CT)‐mediated or ‐coupled J‐aggregates, whose red‐shifts are primarily governed by short‐range orbital interactions, is suggested. Within this framework, the relationship between aggregate structure and functional properties of representative classes of dye aggregates is analyzed for the most advanced OSCs and wavelength‐selective OPDs, providing important insights into the rational design of thin‐film optoelectronic materials. Abstract : J‐ and H‐aggregates constitute archetype functional materials due to unique properties originating from exciton coupling. Here, a broader perspective on the origin of red‐shifted absorption bands including intermolecular charge transfer‐mediated J‐coupling is provided. Further, important classes of dye aggregates with regard to the prevailing intermolecular couplings and their relevance for organic solar cells and photodetectors are analyzed.